The Influence of Capital Structure and Sharia Financing on the Profitability of Micro, Small and Medium Enterprises in the City of Padangsidimpuan - Samsuddin Muhammad (Universitas Muhammadiyah Surabaya, 2023)
This research was conducted to determine the effect of capital structure consisting of own capital, short-term loans, long-term loans and sharia financing on the profitability of micro, small and medium enterprises (MSMEs). This study uses a quantitative approach. The population of this research is all micro, small and medium enterprises in Padangsidimpuan City. Sampling using purposive sampling technique. Respondents who were sampled were small and medium business actors who already had access to bank financing. This study uses multiple linear regression analysis using SPSS software.The results of this study indicate that capital structure simultaneously has a positive and significant effect on the profitability of MSMEs while partially own capital and sharia financing have a positive and significant effect on profitability and short-term debt and long-term debt have an insignificant positive effect on the profitability of MSMEs in Padangsidimpuan City.